Implementasi Enkripsi-Dekripsi dengan Algoritma RC2 Menggunakan Java - Muhammad Iqbal Assegaf; Rahma Destias; Nidhea Sitaresmi; Yudi Wiharto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Cryptography is a security tool used to hide a message. For that we need a security by means of encryption and decryption of data using cryptographic algorithms Rivest Code 2 (RC2). In the cryptographic algorithms Rivest Code 2 (RC2), designed in java programming netbeans which include the ability to operate directly for RC2 algorithm implemented by mode. Specifications architectures and languages into a specified algorithm implementation does not yet support 64-bit operating efficiently. Therefor, instead of using two 64-bit registers as in RC2, RC2 uses four 32-bit registers. Because it uses four registers there will be two rotation operation on each half-round there, and it will also be a lot of bits that will be used to affect the number of bits that are rotated. This multiplication operation is very effective in producing the effect of diffusion or which of course resulted in the deployment of more secure RC2. Android-based application that is generated by utilizing the latest technology